Placoscopana, a new genus of neocoelidiinae (hemiptera: Cicadellidae) from Ecuador - Gonçalves, Clayton Corrêa; Marques-Costa, Ana Paula; Ale-Rocha, Rosaly (Zoologia, 2012)
A new genus of Neocoelidiinae, Placoscopana gen. nov. is proposed and its type-species Placoscopana nigrilinea sp. nov. is described and illustrated based on a male specimen from Ecuador (Orellana Province). Placoscopana gen. nov. is very similar externally to Coronalidia Marques-Costa & Cavichioli, 2007, but differs mainly by the male genitalia: pygopher short with posterior margin approximately truncated; subgenital plates, in dorsal view, with a tuft of setae at apex; and aedeagus with two parallel ventral rows of small spines on the apical half of the shaft. © 2012 Sociedade Brasileira de Zoologia.
Keywords: Cicadellidae; Hemiptera; Neocoelidiinae